Community Detection in Social Networks using Improvised Evolutionary Algorithms - Shakya, Harish Kumar (IIT BHU VARANASI, 2018)
Abstract is available in content.
Keywords: Community Detection in Social Networks; using Improvised Evolutionary Algorithms